The Euro Area Periphery Debt Conundrum - Robin Brooks; Jonathan Pingle (Intereconomics)
Abstract There are many reasons to reform the Stability and Growth Pact, but that reform is no panacea. This is because the euro area periphery has increasingly entered a debt conundrum.